Financial Literacy and Demographics on Financial Behavior of Malang State Polytechnic Students - Yekie Senja Oktora; Yuliati (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of this research is to analyze (1) the influence of financial literacy on financial behavior (2) the effect of gender on financial behavior (3) the effect of age on financial behavior (4) the effect of academic ability on financial behavior (5) the effect of residence on financial behavior . The population in this study were all active D3 students in the Business Administration Study Program, State Polytechnic of Malang, consisting of 547 people. The sample was selected using clustered proportional sampling to obtain a total sample of 116 students. The data of this research are primary data and secondary data. Data were analyzed by multiple regression analysis using SPSS version 25.0. The results of this study are: (1) financial literacy has a positive and significant relationship to behavioral finance (2) gender has a positive and significant relationship to behavioral finance (3) age has a positive and significant relationship to behavioral finance (4) academic ability has a positive relationship and significant on behavioral finance (5) place of residence has a relationship on behavioral finance.